2022
DOI: 10.7717/peerj.12903
|View full text |Cite
|
Sign up to set email alerts
|

The Female Athlete Triad—the impact of running and type of diet on the regularity of the menstrual cycle assessed for recreational runners

Abstract: Background The Female Athlete Triad (FAT) included three interrelated conditions including disordered eating, amenorrhea, and osteoporosis. The American College of Sports Medicine updated the definition of FAT to reflect the interdependence of low energy availability with or without eating disorders. The main aim of the study was to assess the impact of recreational running on potential disturbances in the regularity of women’s menstrual cycles. Additionally, this work compared differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…9 In this study, we used the menstrual cycles reported from a study of 360 young women with menstrual cycles of 21 to 31 days. 29 In addition, a previous study reported that the average age at the onset of menstruation in adolescent women was 12 to 13 years, and menstrual disturbances in puberty should be evaluated after the age of 14, 23 which may have influenced our results. Future studies should analyze the menstrual status of adolescent dancers combined with their individual development.…”
Section: Limitationsmentioning
confidence: 89%
See 1 more Smart Citation
“…9 In this study, we used the menstrual cycles reported from a study of 360 young women with menstrual cycles of 21 to 31 days. 29 In addition, a previous study reported that the average age at the onset of menstruation in adolescent women was 12 to 13 years, and menstrual disturbances in puberty should be evaluated after the age of 14, 23 which may have influenced our results. Future studies should analyze the menstrual status of adolescent dancers combined with their individual development.…”
Section: Limitationsmentioning
confidence: 89%
“…It included information on current age, age at the beginning of pre-professional training, duration of practice outside the curriculum, age at first menstrual period, number of menstrual cycles in the past year, and average menstrual cycle length (short cycles: ≤24 days; normal cycles: 25-31 days; and long cycles: >31 days). 29 However, as menstrual cycle disorders are more prevalent during the first year of menstruation, we excluded dancers in their first year of menstruation from this study. 10 Primary amenorrhea was defined as menophania after the age of 15, whereas secondary amenorrhea was defined as experiencing fewer than 5 or no menstrual periods for at least 3 of the previous 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of artistic or endurance sports may be related to the inclusion criteria of this systematic review, given the young age of the population practicing these sports (i.e., artistic sports), and to the long‐term low BW in those athletes by chronically reducing their energy availability (dietary EI minus the energy expended in exercise < 30 kcal.kgFFM −1 .day −1 ) 23,142–144 . This relative energy deficiency in sport (RED‐S) is not without consequences for the health and performance of athletes (e.g., underweight, irregular periods or amenorrhea in female athletes, illnesses, mood changes, and injuries) 145–147 . As the majority of these sports are practiced by female athletes, the question of the place of women in studies can be asked more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…23,[142][143][144] This relative energy deficiency in sport (RED-S) is not without consequences for the health and performance of athletes (e.g., underweight, irregular periods or amenorrhea in female athletes, illnesses, mood changes, and injuries). [145][146][147] As the majority of these sports are practiced by female athletes, the question of the place of women in studies can be asked more broadly. Indeed, whereas they represented 45% of Olympic athletes in 2016, women represent only 10% of the subjects included in this review, and it clearly points out the importance of considering women and their specificities (body composition and hormonal status) in the studies of sport physiology.…”
Section: Dietary Quality and Nutritional Impact On Body Compositionmentioning
confidence: 99%
“…The two factors, amenorrhea and eating disorders, that come with LEA are also important components called female athlete triad (FAT) ( 10 ). The FAT, which includes amenorrhea, osteoporosis, and an eating disorder, was initially identified in 1992 ( 11 ). Currently, it has been proposed that the FAT can be defined as the existence of one or more elements in females participating in sports ( 11 ).…”
Section: Introductionmentioning
confidence: 99%